METODE MENGGUNTING UNTUK MELATIH KEMAMPUAN MOTORIK HALUS ANAK USIA DINI DI RA AL-IKHWAN KOTA TASIKMALAYA - Nisa Nurhidayah; lukman Hamid; Tina Nurjanah (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2021)
This research is motivated by an unattractive learning style, children often feel bored with the old learning process. The lack of media in learning activities is a big influence for children which should be optimized for all aspects of its development, but it is not fulfilled. This study aims to improve fine motor skills through cutting activities with various media in early childhood in group A RA Al-Ikhwan Tasikmalaya. This research was pre-experimental, with Intec-Group Comparison design. Data collection techniques used in this study were observation. Data collection instruments used observation sheets. The results of the measurement was half the group treated, from 8 children found 3 ones or 37.5% developed very well and 5 children or amounted to 62.5% developed as expected. While the results of the measurement of half the group that were not treated as many as 4 children as expected namely 50.0%, 2 children or 25% of children began to develop, and 2 children who have not developed by 25%. Increasing fine motor skills is said to be effective successfully. This improvement was obtained through cutting activities with various media with learning steps, namely: (1) preparing the media and tools used in cutting activities, (2) giving examples of how to cut according to drawing patterns, (3) distributing media and tools used in cutting activities proportionally for each group, (4) children are allowed to do cutting activities with various media in accordance with the example given by the teacher.